Influence of Mycorrhiza on C:N:P Stoichiometry in Senesced Leaves - Shan-Wei Wu; Zhao-Yong Shi; Ming Huang; Shuang Yang; Wen-Ya Yang; You-Jun Li (Journal of Fungi, 2023)
Senesced leaves play a vital role in nutrient cycles in the terrestrial ecosystem. The carbon (C), nitrogen (N) and phosphorus (P) stoichiometries in senesced leaves have been reported, which are influenced by biotic and abiotic factors, such as climate variables and plant functional groups. It is well known that mycorrhizal types are one of the most important functional characteristics of plants that affect leaf C:N:P stoichiometry. While green leaves’ traits have been widely reported based on the different mycorrhiza types, the senesced leaves’ C:N:P stoichiometries among mycorrhizal types are rarely investigated. Here, the patterns in senesced leaves’ C:N:P stoichiometry among plants associated with arbuscular mycorrhizal (AM), ectomycorrhizal (ECM), or AM + ECM fungi were explored. Overall, the senesced leaves’ C, with 446.8 mg/g in AM plants, was significantly lower than that in AM + ECM and ECM species, being 493.1 and 501.4 mg/g, respectively, which was mainly caused by boreal biomes. The 8.9 mg/g senesced leaves’ N in ECM plants was significantly lower than in AM (10.4 mg/g) or AM + ECM taxa (10.9 mg/g). Meanwhile, the senesced leaves’ P presented no difference in plant associations with AM, AM + ECM and ECM. The senesced leaves’ C and N presented contrary trends with the changes in mean annual temperature (MAT) and mean annual precipitation (MAP) in ECM or AM + ECM plants. The differences in senesced leaves’ C and N may be more easily influenced by the plant mycorrhizal types, but not P and stoichiometric ratios of C, N and P. Our results suggest that senesced leaves’ C:N:P stoichiometries depend on mycorrhizal types, which supports the hypothesis that mycorrhizal type is linked to the evolution of carbon–nutrient cycle interactions in the ecosystem.